Importance of public awareness of hand hygiene and the spread of hand-foot-mouth disease - de Godoy, Gabriela; Cherubim, Guilherme Matheus Bologna; Souza, Cássila Solange Silva Bezerra (Seven Editora, 2023)
It is known that hygiene is a determining factor for the health area, becoming an important marker of social inequality and its habit is responsible for the prevention of infectious diseases such as hand-foot-mouth disease, caused especially in children, but may also affect adults. Therefore, this article aims to discuss the relationship of hand hygiene against the contamination of hand-foot-mouth disease in children and the importance of raising public awareness to prevent its spread. The methodology was based on a Literature Review, where a bibliographic search was performed in the Google Scholar and SciELO databases, where the following descriptors were used: "hand-foot-mouth"; "spread of disease"; "personal hygiene", "child health" and "hand hygiene". In view of the selected descriptors, 30 studies were identified, which went through a screening process where 20 articles were selected, according to the eligibility criteria, for the accomplishment of the present study. It was observed that with prevention and control measures it can reduce the numbers of infected people, as well as prevent the disease from getting worse, so it is extremely relevant to discuss the subject, both by health professionals and academics as well as by the entire local community, in order to prevent this disease from causing greater damage to the individuals present.DOI:https://doi.org/10.56238/globalhealthprespesc-038